THERAPEUTIC AND PROPHYLACTIC EFFECTIVENESS OF TOPICAL IMMUNOMODULATOR IN TREATMENT OF ACUTE RESPIRATORY INFECTIONS - O. V. Shamsheva; N. N. Zvereva (Вопросы современной педиатрии, 2011)
Clinical effectiveness and safety of topical immunomodulator IRS 19 in treatment and prophylaxis of infectious diseases of airways in adults and children was studied in numerous Russian clinical studies. The article reviews the most interesting results of these studies. Administration of bacterial lysates mixture lowers the rate of acute respiratory infections (ARI) and exacerbations of chronic ENT diseases in patients including frequently ailing children. Treatment with the drug results in much smoother disease’s course. Action of a drug shortens terms of a disease, induces significant decrease of ARI complications rate, normalization of nasopharinx biocenose, and lowers the need in antibacterial drugs.